Studies on Autoprothrombin C Thrombin Relationship* - Landaburu, R. H; Abdala, O; Fulginiti, Susana; Curtino, J (Thrombosis and Haemostasis, 1965)
In every prothrombin activation two different enzymatic reactions can be distinguished. The first reaction is the prothrombin disappearance and the second one is the thrombin formation. Autoprothrombin C catalyzes both reactions and thrombin only the first one. The inhibition of thrombin with heparin allows a more complete activation of the thrombin. The two reactions can be independently catalyzed by different substances. Heparin by itself can provide the environment for activation.